ANALISIS PENGAWASAN MELEKAT PADA PEGAWAI NEGERI SIPIL DI KANTOR DINAS KESEHATAN KOTA PALU - Alfiani, Alfiani (Katalogis, 2015)
This research aims at analyzing the supervision of civil servants in Health Department, Palu City. This research uses a qualitative method. This research located on Health Department, Palu City. The informants of this research were taken by using purposive sampling technique and 7 (seven) informants were chosen. The techniques of the data collection are observations, interviews, and documentations. In this research, the researcher uses Milles Hubermen Interpretation approach. This approach is to bring out the meaning and significance of the problems, cases, and situation researched. The result of this research shows that 1. Monitoring. The monitoring has been performed fairly well by the leadership in this regard by the Head of Section, Head of Division, Secretary, Head of Department. 2. Inspection. The inspection by the leadership in this case the Head of Section and Head of Division has been well performed, but not at the secretary and Head of Department. 3. Evaluation. The evaluations conducted by the Head of Section, Head of Division, Secretary, and Head of Department is categorized as well.